Endogenous Endophthalmitis and Liver Abscess: A Metastatic Infection or a Coincidence? - Correia,Catarina (2022)
Abstract Klebsiella pneumoniae is a gram-negative pathogen that is a common cause of severe infections, including pyogenic liver abscess. Dissemination of K. pneumoniae to other organs, including the eye, is associated with significant morbidity and mortality. In the particular case of endogenous endophthalmitis (EE) by K. pneumoniae the prognosis is poor. We report the case of a middle-aged female with K. pneumoniae liver abscess. The patient developed metastatic endophthalmitis that was aggressively treated with systemic antibiotics. The liver abscess resolved with antimicrobials and percutaneous transhepatic drainage, but regarding the endophthalmitis she was discharged from our hospital without recovery of her eyesight. Metastatic spread to the eye should be considered in all patients with liver abscesses who experience ocular signs and symptoms in order to establish a timely diagnosis of EE.